Analysis of Food Street Management Using The RIS3 Method and BPMN Model To Enhance The Competitiveness of Small and Medium Enterprises - Rachmadi, Mohamad Iman; Lukmandono, Lukmandono (Jurnal Teknologi dan Manajemen, 2025)
This research analyzes the management of culinary tourism centers, specifically the Sentra Wisata Kuliner (SWK) Kandangan in Surabaya, using Regional Innovation Strategy for Smart Specialisation (RIS3) and Business Process Modelling Notation (BPMN). The study addresses operational inefficiencies and low visitor engagement, including inventory mismatches, rapid food spoilage, cleanliness issues, and limited payment options. The objective was to identify regional strengths, innovation opportunities, and optimal business processes to enhance competitiveness and efficiency. Employing qualitative methods through case study analysis, data was gathered via field observations, stakeholder interviews, and Focus Group Discussions (FGDs) involving SMEs, government officials, and industry experts. RIS3 facilitated strategic analysis by prioritizing regional strengths, identifying strategic priorities, and engaging stakeholders in entrepreneurial discovery processes. Concurrently, BPMN visually mapped and optimized existing business processes to improve operational clarity. Findings revealed that integrating RIS3 and BPMN significantly enhanced SWK Kandangan’s operational management. The combined methods aligned human resources, production, and financial operations with innovative practices, resolving identified challenges. Consequently, visitor engagement improved, optimizing business sustainability. This study provides valuable insights into applying RIS3 and BPMN methods effectively in regional culinary tourism management, thus supporting SME competitiveness and regional economic growth.